Optimization of Web Server Load Balancing Using HAProxy with the Weighted Round Robin Algorithm - Amalia, Zahrina; Dadi Riskiono, Sampurna (Universitas Negeri Padang, 2025)
The advancement of information and communication technology (ICT) in Indonesia has driven the widespread use of web-based services across various sectors, including education, public services, and digital administration. However, the growing traffic demand is often not supported by adequate server infrastructure, leading to issues such as slow access and system failures. These problems are primarily caused by unbalanced server workloads, especially when relying on a single server or lacking effective load distribution strategies. Load balancing technology is therefore essential to ensure stable and efficient web service performance. This study explores the implementation of the Weighted Round Robin (WRR) algorithm using HAProxy software to distribute loads proportionally based on each server's capacity. The research uses a quantitative experimental method by building a test environment consisting of one HAProxy server and multiple backend servers with different specifications. Traffic simulations are conducted using Apache JMeter to evaluate system performance based on technical metrics such as response time, and request success rate. The results of this study are expected to provide practical solutions for improving the reliability and efficiency of web services, particularly in supporting Indonesia's digital transformation initiatives that are often constrained by limited infrastructure resources.